Aerobic industrial processing of Empeltre cv. natural black olives and product characterisation. (22nd July 2019) - Medina, Eduardo; García‐García, Pedro; Romero, Concepción; de Castro, Antonio; Brenes, Manuel
Summary: The fermentation of natural black olives is currently carried out under anaerobic conditions. This work investigates the aerobic fermentation of this product in tanks containing 16 000 kg of Empeltre olives during two seasons. The microorganisms in brines were yeasts in all cases, whereas lactic acid bacteria growth was only observed in some tanks. Consequently, the pH during fermentation was in most cases higher than recommended 4.3 units. However, the Empeltre olive brines displayed bactericidal effect against Salmonella enterica, Sthapylococcus aureus, Escherichia coli and Listeria monocytogenes, with a 5 log population drop in one or 24 h depending on the brine age so that these olive brines are a harsh environment for the growth of these pathogens. It was found HyEDA as the major phenolic compound in both brine and olive pulp at the beginning of fermentation that slowly hydrolysed into hydroxytyrosol that reached a concentration up to 1500 mg kg −1 . Abstract : Industrial aerobic fermentation of natural black olives.